ASSOCIATION OF DISEASE HISTORY WITH RHEGMATOGENOUS RETINAL DETACHMENT AMONG PATIENTS IN DEPARTMENT OF OPHTHALMOLOGY AT DR. MOHAMMAD HOESIN ACADEMIC GENERAL HOSPITAL PALEMBANG - Septadina, Indri Seta; Putri, Dwi Octaverina; Amin, Ramzi (Buletin Farmatera, 2019)
Abstract. Retinal detachment is the detachment of neuroretina from pigmented retinal epithelial layer which supplying it. Retinal detachment which is untreated could lead into permanent visual impairment. According to its etiology, retinal detachment can be classified into rhegmatogenous and non-rhegmatogenous, where rhegmatogenous cause is more common that the other. Rhegmatogenous retinal detachment is associated with many previous disease history. Research was to determine the association between previous disease history and rhegmatogenous retinal detachment in the patient in Department of Ophthalmology at Dr. Mohammad Hoesin Academic General Hospital, Palembang. This was an analytical observational study using cross sectional design. Population of study was patients which had been diagnosed as having retinal detachment at the study site. One hundred and fifty-five of 267 patients were taken as study sample by using consecutive sampling technique. Data was obtained from patients’ medical records from 1 January 2015 to 31 August 2018. Analysis of association showed the following results: previous cataract surgery (p=0,038; PR=1,309), high degree myopia (p=0,014; PR=1,400) and trauma history (p=0,036; PR=1,350). There were significant associations between previous cataract surgery, high degree myopia and trauma history with rhegmatogenous retinal detachment.Keywords: Previous cataract surgery, myopia, trauma, rhegmatogenous retinal detachment.